Porti e approdi fluviali in Italia peninsulare : dall'età romana all'anno mille - Luciano, Alessandro (Archaeopress archaeology., 2019)
Most Roman ports were located at river mouths and/or in lagoon areas and were connected with inland areas by rivers or artificial canals. For this reason, port structures (piers and warehouses) were set at some distance from the sea, as in Rome (Emporium of Testaccio along the Tiber), in Pisa-San Rossore and in the Po valley. According to historical sources, many river wharves were located along the Po while San Vincenzo abbey managed the Volturno river. The Carolingian river wharves of San Vincenzo were composed of timber, stone and, according to the Roman tradition, concrete structures. A slow recovery of maritime trades is already evident in the Carolingian Age. This book analyses the Roman and early medieval ports of Italy and the building techniques used in their structures; it displays the elements of continuity and discontinuity revealed during these centuries.